Effect of Aggregate Crystalline Surface Anisotropy on Asphalt–Aggregate Interface Interaction Based on Molecular Dynamics - Jian Li; Liang He (Applied Sciences)
To investigate the influence of aggregate crystalline surface anisotropy on the interfacial effects and understand the bonding mechanisms, molecular dynamics simulations were employed to analyze the spatial distribution, diffusion, and adhesion properties of asphalt on typical acidic (α-quartz, SiO2) and weakly alkaline (calcite, CaCO3) aggregates. The results indicated that different types and crystalline surfaces of aggregates did not alter the distribution patterns of the asphalt components on their surfaces. However, the magnitude of the radial distribution function (RDF) varied with different crystalline surfaces, and a higher RDF value was correlated with better adhesion performance. Different diffusion behaviors were exhibited by asphalt molecules on different crystalline surfaces: slower diffusion was correlated with stronger adhesion and faster diffusion with weaker adhesion. The adhesion performance was significantly affected by the anisotropy of the aggregates. In the asphalt–SiO2 system, the van der Waals energy and surface atomic density were the major influencing factors, whereas, in the asphalt–CaCO3 system, the electrostatic energy was significantly influenced by ionic bonding. Overall, alkaline aggregates showed greater adhesion performance with asphalt than acidic aggregates.